Sugar-Sweetened Beverage Intake Is Positively Associated with Baseline Triglyceride Concentrations, and Changes in Intake Are Inversely Associated with Changes in HDL Cholesterol over 12 Months in a Multi-Ethnic Sample of Children. Issue 10 (2nd September 2015) - Van Rompay, Maria I; McKeown, Nicola M; Goodman, Elizabeth; Eliasziw, Misha; Chomitz, Virginia R; Gordon, Catherine M; Economos, Christina D; Sacheck, Jennifer M
Abstract: Background: Intake of sugar-sweetened beverages (SSBs) is linked to greater cardiometabolic risk in adults. Although longitudinal evidence is sparse among children, SSB intake reduction is targeted to reduce cardiometabolic risk factors in this group. Objective: We investigated characteristics associated with consumption of SSBs in a multi-ethnic sample of children/adolescents and measured cross-sectional and longitudinal associations between SSB intake and plasma HDL cholesterol and triglycerides (TGs) over 12 mo. Methods: In a diverse cohort of children aged 8–15 y, cross-sectional associations ( n = 613) between baseline SSB intake and blood lipid concentrations and longitudinal associations ( n = 380) between mean SSB intake, changes in SSB intake, and lipid changes over 12 mo were assessed with multivariable linear regression. Results: Greater SSB intake was associated with lower socioeconomic status, higher total energy intake, lower fruit/vegetable intake, and more sedentary time. In cross-sectional analysis, greater SSB intake was associated with higher plasma TG concentrations among consumers (62.4, 65.3, and 71.6 mg/dL in children who consumed >0 but <2, ≥2 but <7, and ≥7 servings/wk, respectively; P- trend: 0.03); plasma HDL cholesterol showed no cross-sectional association. In the longitudinal analysis, mean SSB intake over 12 mo was not associated with lipid changes; however, the 12-mo increase in plasma HDL-cholesterol concentration was greater among children who decreased their intake by ≥1 serving/wk (4.6 ± 0.8 mg/dL) compared with children whose intake stayed the same (2.0 ± 0.8 mg/dL) or increased (1.5 ± 0.8 mg/dL; P = 0.02). Conclusions: In a multi-ethnic sample of children, intake of SSBs was positively associated with TG concentrations among consumers, and changes in SSB intake were inversely associated with HDL cholesterol concentration changes over 12 mo. Further research in large diverse samples of children is needed to study the public health implications of reducing SSB intake among children of different racial/ethnic groups. The Daily D Health Study was registered at clinicaltrials.gov as NCT01537809.